OS CAÇADORES DO RIOZINHO DO ANFRÍSIO: SABERES E PRÁTICAS CULTURAIS ENTRE NARRATIVAS E IMAGENS. - Flávio Bezerra Barros (Nepan editor, 2017)
This article illustrates the traditional knowledges and the cultural practices associated to hunting activity developed by the riverine population of the Riozinho do Anfrísio Extractive Reserve in Altamira municipality, in the state of Pará. The text is developed according to an ethnographic perspective and uses methods such us open interviews and participant observation. In the observed context, hunting constitutes one of the main productive activities of the social agents and presents itself as being permeated by symbolic elements. Curupira, Mapinguari and Matinta Pereira are examples of the superhuman entities that operate to regulate the action of the hunters. The hunted animals are utilised in many ways, in that they function as food as well as being employed in the preparation of remedies and in practices of magic.